Factors Affecting Prognosis in Hypoxic Encephalopathy Patients Followed-up in Intensive Care Unit - Nesrin Helvacı Yılmaz; Cem Erdoğan; Deniz Kızılaslan; Özge Arıcı Düz; Eren Toplutaş; Lütfü Hanoğlu (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:Hypoxic encephalopathy (HE) after cardiac arrest is a clinical condition that can cause severe neurological sequelae and death. It is important to determine the prognosis in patients with HE for follow up and developing future treatments in the long term. Our aim was to investigate the effects of age, gender, hypothermia, lesion site in brain magnetic resonance imaging (MRI), seizure and electroencephalography (EEG) findings on prognosis in patients with the diagnosis of HE.Materials and Methods:The data of the adult intensive care unit was evaluated retrospectively. A total of 194 patients with HE were included into the study. One hundred and eighteen (60.8%) of the patients were male and 76 (39.2%) were female. The survivors and those who died were identified. Hypothermia therapy, brain MRI findings (cortical and/or subcortical lesion), presence of seizures (myoclonic, generalized, focal) and EEG findings (epileptic activity, status, generalized slowing) were recorded.Results:The mean age was 59.46±1.71 (18-89). Seventy-six (39.2%) patients underwent hypothermia. One hundred and seven (55.2%) patients died. The rate of exitus in elderly patients was significantly higher (p<0.01). The brain MRI of 88 patients showed hypoxic lesions (cortical in 8 patients, subcortical in 21 patients, cortical + subcortical lesion in 59 patients). The survival rate of the patients with cortical or subcortical pathology is significantly higher than patients with both pathology (p<0.01). As a result of multiple regression analysis, a 1-year increase in age, increased the risk of death by 4%, while the presence of pathological findings in both areas in brain MRI increased the risk of death by 2.62 times. There was no significant difference of gender, hypothermia, seizures and pathological EEG findings on survival (p>0.05).Conclusion:Approximately half of the patients included in our study died. The survival rate of the elderly patients and the patients with multiple lesions in brain MRI was low.